THE GIVING OF MODRINISTIC TECHNIQUES IN VIRGINIA WOOLF’S NOVEL " MRS. DELOUEY - Rashidova Saida (Galaxy International Interdisciplinary Research Journal, 2023)
In a speech work, one of the semiotic means used "by definition", in accordance with a certain set of rules, is punctuation. Like any other sign, a punctuation mark is a two-sided entity, a function of two functives (an expression function and a content function).